PENERAPAN TEKNOLOGI DALAM MEMAKSIMALKAN PENJUALAN TEH DI INDONESIA - Desi Putriani; Dessyana Kardha (JURNAL ILMIAH AGRINECA, 2020)
Tea is one of the leading agricultural commodities in Indonesia as the seventh largest tea producer in the world. Today's drinks are still consumed by many people as a refreshing drink or medicine. An infusion made by brewing leaves, shoots, or leaf stems dried from the Camellia sinensis plant with hot water. The purpose of this study is to build a sales application that is able to maximize tea sales so as to preserve tea production in the agricultural sector in Indonesia. In building the system the method of approach used is the waterfall method. Data collection methods by interview, observation and library methods. Using PIECES analysis and flowchart design, data Flow Diagrams and Entity Relationship Diagrams using java script, html, and php technology. The results of this research are making a tea-selling application on mobile-based yellow gambyong tea that can make it easier for people to make product purchases in the internet era and make it easier for tea businesses to manage and develop their businesses.